1979
DOI: 10.5006/0010-9312-35.2.45
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ferrite Content on Stress Corrosion Cracking in Duplex Stainless Steel Weld Metals at Room Temperature

Abstract: Constant extension rate tests have been conducted on Type 304 stainless steel base metal specimens and on stainless steel weld metal specimens with ferrite contents of Ferrite Number 1, 3, 6, 11, 16, and 24, at room temperature in deaerated, 1 N HCI. Stress corrosion cracking in wholly austenitic Type 304 base metal occurs transgranularly, while cracking in duplex weld metal occurs either by the combined action of stress assisted ferrite dissolution and stress corrosion cracking (SCC) in the austenite or entir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Due to metallurgical changes in weld interface, phase changes in delta ferrite formations, grain boundary corrosion and sigma phase will arise. For avoiding this, pre-and postheat treatment are needed to prevent the metallurgical defects [3][4][5][6][7]. Moreover, joining of austenitic stainless steel under cryogenic or corrosive environment, the ferrite quantity to be minimized or controlled to avoid property degradation during service.…”
Section: Problems In Fusion Welding On Stainless Steelmentioning
confidence: 99%
“…Due to metallurgical changes in weld interface, phase changes in delta ferrite formations, grain boundary corrosion and sigma phase will arise. For avoiding this, pre-and postheat treatment are needed to prevent the metallurgical defects [3][4][5][6][7]. Moreover, joining of austenitic stainless steel under cryogenic or corrosive environment, the ferrite quantity to be minimized or controlled to avoid property degradation during service.…”
Section: Problems In Fusion Welding On Stainless Steelmentioning
confidence: 99%
“…Baeslack et al,66) found that the addition of nitrogen to welds of SUS 304 stainless steel decreased the resistance to SCC in MgCl 2 (see Fig. 15).…”
Section: Corrosion Propertiesmentioning
confidence: 99%
“…Given this solid-state segregation, the phase balance and amount of segregation will be controlled by factors including the cooling rates for castings and weldments, whereas the thermo-mechanical processing conditions and annealing treatment are very important for wrought products. Additionally, the solidification of duplex weldments occurring in the single-phase ferritic mode largely influences the precipitation of other phases [52][53][54].…”
Section: Precipitation Of Other Phasesmentioning
confidence: 99%